Performance improvement of proton exchange membrane electrolyzer cells by introducing in-plane transport enhancement layers. (1st September 2019) - Kang, Zhenye; Yu, Shule; Yang, Gaoqiang; Li, Yifan; Bender, Guido; Pivovar, Bryan S.; Green, Johney B.; Zhang, Feng-Yuan
Abstract: Thin/tunable liquid/gas diffusion layers (TT-LGDLs) or porous transport layers (TT-PTLs), have exhibited superior multifunctional performance in proton exchange membrane electrolyzer cells (PEMECs), which can be attributed to their unique structures, such as planar surface, straight-through pores, thin thickness, etc. For achieving better PEMEC performance, TT-LGDLs with smaller pore size are desired. However, in this case, mass diffusion issues are brought in when some of the pores are covered by the flow field lands or shoulders. The coverage of the pores can lead to very high transport resistance, which may reduce the number of active oxygen evolution reaction sites, and therefore lower down the PEMEC performance. The in-plane transport enhancement layer for TT-LGDLs/PTLs are proposed to develop a dual-layer LGDL/PTL structure for improving the mass diffusion and the PEMEC performance. The results of this research reveal that the dual-layer LGDL/PTL structure exhibits smaller ohmic resistance and mass transport resistance, and therefore improve the PEMEC performance, without obvious changes in kinetic losses. The total ohmic resistance and mass transport resistance can be reduced by about 23% and 41%, respectively, with an ∼830 μm pore TT-LGDL/PTL stacking on a ∼100 μm pore TT-LGDL/PTL. The results indicate the feasibility of stacking the in-plane transport enhancement layer with large pore sizes onto a small pore TT-LGDLs/PTLs for high efficiency and low cost PEMEC practical applications. Graphical abstract: Image 107665 Highlights: In-plane mass transport limitation of the novel TT-LGDLs are investigated. Approaches for alleviating transport limitation are proposed and tested. An enhancement layer can promote mass transfer capability and PEMEC performance. The PEMEC performance enhancement is due to the reduced ohmic and diffusion losses.